The Buddhist Concept of Paṭiccasamuppāda Based on Pāli Manuscripts: Genesis, Meanings, Annotated Translation, Interpretation, and Doctrinal Significance - Chowdhury, Sanjoy Barua (Poligrafi, 2022)
The concept of Paṭiccasamuppāda is regarded as one of the most profound and subtle teachings imparted by the historical Buddha (563–483 BCE) since the inception of his teachings. In addition to its doctrinal record in the mainstream Buddhist languages of the Pāli and Sanskrit traditions, the Buddhist concept of Paṭiccasamuppāda has been evolved by numerous scholars over 2600 years and contributed to uplifting doctrinal components in many dialects in South and Southeast Asia. Prior to the Pāli tradition and Nikāya manuscripts, the paper aims to clarify the genesis of Paṭiccasamuppāda, including its meaning, annotated translation, interpretation, and doctrinal significance. An in-depth study of this research reveals why and to what degree the Pāli tradition values the thought of Paṭiccasamuppāda as articulating its insight on how to attain the path of ultimate liberation from a Buddhist perspective.